Amino acid abundance and composition in cell culture medium affects trace metal tolerance and cholesterol synthesis - Rawat, Jyoti; Bhambri, Aksheev; Pandey, Ujjiti; Banerjee, Sanchita; Pillai, Beena; Gadgil, Mugdha (Biotechnology Progress, 2023)
Amino acid compositions of cell culture media are empirically designed to enhance cell growth and productivity and vary both across media formulations and over the course of culture due to imbalance in supply and consumption. The interconnected nature of the amino acid transporters and metabolism suggests that changes in amino acid composition can affect cell physiology. In this study, we explore the effect of a step change in amino acid composition from a DMEM: F12-based medium to a formulation varying in relative abundances of all amino acids, evaluated at two amino acid concentrations (lean LAA vs. rich HAA). Cell growth was inhibited in LAA but not HAA. In addition to the expected effects on expression of the cell cycle, amino acid response and mTOR pathway genes in LAA, we observed an unanticipated effect on zinc uptake and efflux genes. This was accompanied by a lower tolerance to zinc supplementation in LAA but not in the other formulations. Histidine was sufficient but not necessary to prevent such zinc toxicity. Additionally, an unanticipated downregulation of genes in the cholesterol synthesis pathway was observed in HAA, accompanied by an increase in cellular cholesterol content, which may depend on the relative abundances of glutamine and other amino acids. This study shows that changes in the amino acid composition without any evident effect on growth may have profound effects on metabolism. Such analyses can help rationalize the designing of medium and feed formulations for bioprocess applications beyond replenishment of consumed components.
Keywords: Amino acids; cell culture medium; CHO cells; Cholesterol; zinc

Leveraging machine learning to dissect role of combinations of amino acids in modulating the effect of zinc on mammalian cell growth - Pandey, Ujjiti; Madhugiri, Indrani; Gadgil, Chetan; Gadgil, Mugdha (BIOTECHNOLOGY PROGRESS, 2024)
Keywords: Absorption; Cytotoxicity; ENTEROCYTES; HISTIDINE